Réponses

2014-01-05T15:33:34+01:00
Meilleure réponse !
2014-01-05T15:35:29+01:00
(x-3)(4x-5)=15(x-3) (4x-5) -15=0

4x² - 5x -12x +15 - 15 = 0
4x² - 17x = 0

delta = 289
racine(delta) = 17

x1 = (-b+racine(delta))/2a = 4,25

x2 = (-b-racine(delta))/2a = 0

Donc les solutions sont {0;4,25}
?*
( x - 3)(4x - 5) = 15
4x² - 5x - 12x + 15 = 15
4x² - 5x - 12x = 15 - 15
4x² - 7x = 0
x(4x - 7) = 0
x = 0 ou 4x - 7 = 0
x = 0 ou 4x = 7
x = 0 ou x = 7/4
Il manque un 1 dans mon commentaire précédent !!!
( x - 3)(4x - 5) = 15
4x² - 5x - 12x + 15 = 15
4x² - 5x - 12x = 15 - 15
4x² - 17x = 0
x(4x - 17) = 0
x = 0 ou 4x - 17 = 0
x = 0 ou 4x = 17
x = 0 ou x = 17/4
Merci beaucoup, merci